Investigating the Effectiveness of Coal-Fired Power Plant Operations: Management, Technical and Air Pollution Aspects - Ramly, Zamzam T. A.; Ishak, Mohd Y.; Abdullah, Ahmad M.; Ismail, Marzuki; Abdullah, Samsuri; Abu Mansor, Amalina (Ital Publication, 2025)
Coal-fired energy has been a major part of Malaysia's power supply, causing environmental pollution and slowing sustainable growth. To address these issues, we evaluated a coal-fired power plant's efficiency using a questionnaire completed by industry experts. This study seeks to find factors affecting coal-fired power generation efficiency and create a statistical model. The questionnaire covered five areas: best management practices, technology efficiency, cost efficiency, fuel efficiency, air pollution control, and the best available technique. Principal Component Analysis (PCA) was used to simplify large data sets. The results showed that 15 principal components were valid, with a KMO value of 0.836 (greater than 0.50) and a Bartlett Test value below 0.05. The results show a strong correlation between the best available technique and various indicators: best management practice (r=0.614, p<0.01), technology efficiency (r=0.719, p<0.01), cost efficiency (r=0.529, p<0.05), fuel efficiency (r=0.662, p<0.01), and air pollution control efficiency (r=-0.752, p<0.01). The model indicates that verifying the standard operating procedure (SOP) is crucial for improving power generation efficiency and reducing human error (R²=0.914). This study pinpoints issues reducing power plant efficiency, particularly regarding emissions, and shows that the regression model is strong (R² = 0.916–0.647). It will assist policymakers and researchers in creating sustainable environmental management plans. Doi: 10.28991/ESJ-2025-09-01-06 Full Text: PDF